2022
DOI: 10.1002/aisy.202200020
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Memristance and Negative Differential Resistance in Point‐Contacted Metal–Oxides–Metal Heterojunctions: Role of Oxygen Vacancy Electromigration and Electron Hopping

Abstract: Nonvolatile resistive switching memristance devices with a high on/off ratio are desirable for nanoelectronics such as resistive random‐access memory (RRAM) and in‐memory computing. Here, bipolar resistive switching in point‐contacted W/LaAlO3/SrTiO3(111) heterojunctions is reported, in which a Schottky barrier is formed at the metal/oxides interface, and 2d electron gas is formed at the interface of perovskite oxides. A negative differential resistance is observed in the RESET process. The result shows that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In other reports, the V O migration upon a certain external field has been confirmed to be an important origin of such ferroelectric-like behavior, and the amorphous state of HfO 2 facilitates the migration of V O as the influence of the built-in electric field in the crystalline lattice is avoided. Although the ferroelectricity can mostly be seen in crystalline structures and can be weakened in a more disorganized structure, the amorphous HfO 2 has also been reported to obtain a similar behavior. , The amorphous state can depress the strength of ferroelectricity, but the V O migration here provides another origin of polarization switching . As thinner thickness and higher temperature facilitate V O migration and recombination with O 2 , the latter causes a weakened ferroelectric-like feature.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In other reports, the V O migration upon a certain external field has been confirmed to be an important origin of such ferroelectric-like behavior, and the amorphous state of HfO 2 facilitates the migration of V O as the influence of the built-in electric field in the crystalline lattice is avoided. Although the ferroelectricity can mostly be seen in crystalline structures and can be weakened in a more disorganized structure, the amorphous HfO 2 has also been reported to obtain a similar behavior. , The amorphous state can depress the strength of ferroelectricity, but the V O migration here provides another origin of polarization switching . As thinner thickness and higher temperature facilitate V O migration and recombination with O 2 , the latter causes a weakened ferroelectric-like feature.…”
Section: Resultsmentioning
confidence: 91%
“…21,37 The amorphous state can depress the strength of ferroelectricity, but the V O migration here provides another origin of polarization switching. 38 As thinner thickness and higher temperature facilitate V O migration and recombination with O 2 , the latter causes a weakened ferroelectric-like feature. We believe that this further proves the significance of V O in our system, not only for the metallic conduction but its migration also leads to obvious ferroelectric-like behavior.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The current increases only slightly as the voltage is then increased to −2.5 V, and the device remains in HRS for the duration of the voltage increase from −2.5 to 0 V. The above situation indicates that the coexistence of RS and NDR behavior occurs in devices with a functional layer deposition time of 60 min, which may be caused by the migration of defects (such as oxygen vacancies) in the functional layer. 37,38 The NDR- coupled RS behavior at room temperature makes the device promising for applications in bionic computing, 39 multifunctional devices, 40 and nonvolatile multilevel memory devices. 41 When the deposition time of the La 0.7 Sr 0.3 MnO 3 film increases to 90 min, the NDR effect in the device begins to decay.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Several reports have noted and explained the NDR effect in memristors. 25,26 Hu et al reported that lower power consumption and faster switching time for NDR can be achieved in the Ag/TiO x /FTO memristor, where the NDR effect is due to compensation and synergy among the conductive filaments (CFs). 25 Gan et al found that NDR is observed in the RESET process of the W/LaAlO 3 /SrTiO 3 /Pt memristor, and they believed that the NDR effect is strongly associated with oxygen vacancies in oxides, with a dominant contribution from electron hopping.…”
Section: Introductionmentioning
confidence: 99%
“…25 Gan et al found that NDR is observed in the RESET process of the W/LaAlO 3 /SrTiO 3 /Pt memristor, and they believed that the NDR effect is strongly associated with oxygen vacancies in oxides, with a dominant contribution from electron hopping. 26 The frequency of the oscillation circuit depends on the degree of NDR, so it is necessary to establish a conductive model to achieve adjustable NDR effects. Key factors, such as repeated scanning times, multiple charge transport mechanisms, and the selection of memristor materials, should also be considered, but receive little attention.…”
Section: Introductionmentioning
confidence: 99%